Thermal performance and heat transfer enhancement of parabolic trough receivers – numerical investigation, thermodynamic and multi-objective optimisation - Bello-Ochende, Tunde (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.